An Efficient Clustered Regularly Interspaced Short Palindromic Repeat (CRISPR)/CRISPR-Associated Protein 9 Mutagenesis System for Oil Palm (Elaeis guineensis) - Wan-Chin Yeap (Frontiers Media S.A., 2021)
The clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein 9 (Cas9) system has emerged as a powerful tool for the precise editing of plant genomes for crop improvement. Rapid in vitro methods for the determination of guide RNA (gRNA) cleavage efficiency and an efficient DNA delivery system is essential for gene editing. However, we lack an efficient gene-editing system for palm species. In this study, we described the development of a transient oil palm protoplast assay to rapidly evaluate the cleavage efficiency of CRISPR/Cas9 mutagenesis and the generation of stable transformed oil palms using biolistic particle bombardment in immature embryos. Using the phytoene desaturase (EgPDS) gene, we found cleavage frequency of up to 25.49% in electro-transfected protoplast, which enables the production of transgenic oil palm shoots exhibiting chimeric albino phenotypes as a result of DNA insertions, deletions (InDels), and nucleotide substitutions, with a mutation efficiency of 62.5–83.33%. We further validated the mutagenesis efficiency and specificity of the CRISPR/Cas9 system in oil palm by targeting the brassinosteroid-insensitive 1 (EgBRI1) gene, which resulted in nucleotide substitutions in EgBRI1 with premature necrosis phenotype in oil palm transgenic shoots and stunted phenotype resulting from DNA InDels. Taken together, our results showed that effective and efficient editing of genes using the CRISPR/Cas9 system can be achieved in oil palm by optimizing the selection of efficient gRNA and DNA delivery methods. This newly designed strategy will enable new routes for the genetic improvement in oil palm and related species.